Needlework - Sullivan, Deirdre (Dublin: Little Island, 2016)
Powerful, poetic and disturbing, Needlework is a girl's meditation on her efforts to maintain her bodily and spiritual integrity in the face of abuse, violation and neglect
Keywords: Fiction